Transposing Military Role Amidst Covid-19 Pandemic in Southeast Asia (Sociología y tecnociencia, 2023)
Military engagement in response to COVID-19 crisis has been a policy discourse since the breakout of the pandemic in early 2020 worldwide. While the extent to which the military engagement of COVID-19 responses remains contentious, we identify the ways in which Southeast Asian countries have employed troops in dealing with the public health crises and challenges. Aimed to measure how deep military engagements in the COVID-19 responses in Southeast Asia have been, we developed the typology of military responses during COVID-19 pandemic by Passos and Aćacio. We discovered that military involvement is impacted by governance capacity, especially health care system, rather than political strength. A country that has weak in health care capacity tends to engage military in fighting against COVID-19.Military engagement in response to COVID-19 crisis has been a policy discourse since the breakout of the pandemic in early 2020 worldwide. While the extent to which the military engagement of COVID-19 responses remains contentious, we identify the ways in which Southeast Asian countries have employed troops in dealing with the public health crises and challenges. Aimed to measure how deep military engagements in the COVID-19 responses in Southeast Asia have been, we developed the typology of military responses during COVID-19 pandemic by Passos and Aćacio. We discovered that military involvement is impacted by governance capacity, especially health care system, rather than political strength. A country that has weak in health care capacity tends to engage military in fighting against COVID-19.
Keywords: Transposing, Military, Covid-19, Pandemic